Evaluation of the impact of severity of itching symptoms on the level of depression in patients with allergic contact eczema (preliminary study) - Czarny-Działak, Małgorzata; Latała-Łoś, Ewa (Medical Studies/Studia Medyczne, 2014)
Introduction : Allergic contact dermatitis is one of the most frequent skin disorders in the general population as well as among people who work professionally. Allergic contact allergens are simple chemical compounds. The most common are nickel and fragrance substances. Aim of the research : To estimate if and how the degree of itching in allergic contact dermatitis influences the development of depression. Material and methods: The treatment was conducted on a group of 17 people with allergic contact dermatitis. Each person was treated in order to estimate the level of depression using Becks scale and the level of itching. Next, it was estimated if the level of itching had any influence on the development of depression. Results: All skin diseases, including allergic contact eczema affect the biological and psychosocial functioning, and the quality of human. Five patients out of 17 showed features of depression: 3 mild (2 men and 1 woman), which is the most common state of transition, and 2 (women) moderately-severe depressive symptoms. Both patients with moderately-severe depressive symptoms had a significant degree of severity of pruritus. Conclusions: It was stated that the level of itching has no influence on the development of depression.